Cytopathology and immune response in the hepatopancreas of decapod crustaceans - Vogt, Günter (Diseases of aquatic organisms, 2020)
The hepatopancreas of decapod crustaceans is used as an example to illustrate the range of cytopathologies, detoxification mechanisms, and immune responses that environmental toxicants and pathogens can induce in a single organ. The hepatopancreas is the central metabolic organ of decapods and consists of hundreds of blindly-ending tubules and intertubular spaces. The tubular epithelium contains 5 structurally and functionally different cell types, and the interstitium contains haemolymph, haemocytes, connective tissue, and fixed phagocytes. Some physiological conditions such as moulting and starvation cause marked but reversible ultrastructural alterations of the epithelial cells. Environmental toxicants induce either detoxification mechanisms or structural damage in cells, depending on toxicant and concentration. The hepatopancreas is also a main target organ for pathogens, mainly viruses, bacteria, and protists that enter the body via the digestive tract and gills and replicate in the hepatopancreatocytes. The cytopathologies caused by toxicants and pathogens affect single cell types specifically or, more often, several cell types simultaneously. Pathogenesis often begins in a certain cell organelle such as the nucleus, mitochondrion, or endoplasmic reticulum, spreads to other organelles, and ends with death of the infected cell. Fixed phagocytes in the interstitium capture and degrade pathogens that move from the infected tubules into the intertubular spaces or enter the hepatopancreas via circulation. Relatively few disease agents elicit the melanisation and encapsulation reaction that encloses infected tubules by a rigid melanised capsule and kills the entrapped pathogens.
Gesehen am 04.06.2020